Wakaf Linked Sukuk Dalam Perspektif Maqashid Syariâ€™ah - Fad, Mohammad Farid (Journal of Islamic Studies and Humanities, 2021)
Based on BWIâ€™s data, the potential for wakaf money in Indonesia reaches at least IDR 180 trillion (www.gomuslim.co.id, 2017) per year. But in reality, the assets of large waqf funds are not necessarily linear with the level of welfare of the Muslim community in Indonesia. In addition, it is necessary to revitalize the endowment of money to revive its vital role. One way is to collaborate between Sukuk and money waqf agreements. The Waqf Linked Sukuk (WLS) can be seen as an ongoing financing instrument that Islam is trying to help maintain the ratio of public spending from, for and by the people. Furthermore, WLS can be an important innovation for economic sustainability, especially to finance micro-communities without interest rates. Whereas the WLS contract needs to be reviewed in favor of the public benefit from the perspective of maqashid shari'ah. This research uses a qualitative approach. Data collection methods used in this study are literature, documentation and interview methods. In analyzing the data that has been collected, researchers will use descriptive-analytical analysis with the ushuliyah approach. The results of this study are waqf and sukuk which consist of 2 different product orientations, namely Tabarru and Tijaroh, which are transformed and correlated in an effort to realize greater benefit value. The legal basis for allowing this WLS product is Q.S. Al-Maidah verse 1, Q.S. al-Isra 'verse 34, Q.S. Al-Baqarah verse 275, the hadith of the Prophet, fiqh rules are "basically, all muamalah is permitted unless there is an argument that forbids it", fiqh rules "should not endanger yourself or others, basically, all forms of muamalah may be done unless there is an argument which is prohibited forbid it ", the statement of DSN-MUI Number B-109 / DSN-MUI / II / 2019 concerning the Statement of Shari'ah Cash Waqf Linked Sukuk and the principle of" an act (regulation) of the government, having the core guaranteed the interests and welfare of its people ". The WLS product when viewed from the perspective of the shariah maqashid is very much in accordance with the six elements of the maqashid shariah.Keywords: cash waqf, sukuk, the maqashid shariâ€™ah.Â AbstrakBerdasarkan penghitungan BWI, potensi wakaf uang di Indonesia setidaknya mencapai Rp 180 triliun (www.gomuslim.co.id, 2017) per tahun. Namun kenyataannya, aset wakaf uang yang besar ternyata belum tentu linier dengan tingkat kesejahteraan bagi komunitas Muslim di Indonesia. Selain itu, perlu revitalisasi wakaf uang guna menghidupkan kembali peran vitalnya. Salah satu caranya adalah dengan mengkolaborasikan antara Sukuk dan akad wakaf uang. Wakaf Linked Sukuk (WLS) dapat dipandang sebagai instrumen pembiayaan berkesinambungan yang coba diajukan oleh Islam guna membantu mempertahankan rasio belanja publik dari, untuk dan oleh rakyat. Lebih lanjut, WLS bisa menjadi inovasi penting untuk keberlanjutan ekonomi, khususnya untuk membiayai masyarakat mikro tanpa suku bunga. Padahal akad WLS perlu ditinjau keberpihakannya pada kemaslahatan publik dari perspektif maqashid syariâ€™ah. Penelitian ini memakai pendekatan kualitatif. Metode pengumpulan data yang dipakai dalam penelitian ini adalah metode literature, dokumentasi dan interview. Dalam menganalisis data yang telah terkumpul, peneliti akan menggunakan analisis deskriptif-analitis dengan pendekatan ushuliyah. Adapun hasil penelitian ini ialah wakaf dan sukuk yang terdiri atas 2 orientasi produk yang berbeda yaitu akad tabarru dan tijaroh, yang ditransformasikan dan dikorelasikan dalam upaya mewujudkan nilai kemaslahatan yang lebih besar. Adapun landasan hukum diperbolehkannya produk WLS ini ialah Q.S. Al-Maidah ayat 1, Q.S. al-Israâ€™ ayat 34, Q.S. Al-Baqarah ayat 275, hadis Nabi, kaidah fikih yang â€œpada dasarnya, semua muamalah diperbolehkan kecuali ada dalil yang mengharamkannyaâ€, kaidah fikih â€œtidak boleh membahayakan diri sendiri maupun orang lain, pada dasarnya, semua bentuk muamalah boleh dilakukan kecuali ada dalil yang mengharamkannyaâ€, pernyataan DSN-MUI Nomor B-109/DSN-MUI/II/2019 tentang Pernyataan Keselarasan Syariâ€™ah Cash Waqf Linked Sukuk serta kaidah â€œsuatu tindakan (peraturan) pemerintah, berintikan terjaminnya kepentingan dan kemaslahatan rakyatnyaâ€. Produk WLS bila ditinjau dari perspektif maqashid syariâ€™ah amatlah sesuai dengan keenam unsur maqashid syariâ€™ah.Kata Kunci: wakaf uang, sukuk, maqashid syariâ€™ah